Surface layer of Pt‐O‐Ce bonds on CeOx nanowire with high ORR activity converted by proton beam irradiation. Issue 5 (16th January 2021) - Chauhan, Shipra; Mori, Toshiyuki; Kobayashi, Tomohiro; Yamamoto, Shunya; Ito, Shigeharu; Auchterlonie, Graeme; Wepf, Roger; Ueda, Shigenori; Ye, Fei
Abstract: To develop the state‐of‐the‐art polymer membrane fuel cells. Both maximization of oxygen reduction reaction (ORR) activity on Pt cathode and minimization of Pt content in the cathode are required. For this challenge, the defect interface on oxide support was modified by proton beam irradiation method. Pt‐CeOx nanowire/C (Pt/C = 0.02) was fabricated using the proton beam irradiation method. Since the radical density generated by proton beam irradiation is two orders of magnitude greater than that of electron beam irradiation, the CeOx nanowire surface was fully converted to a thin layer of Pt‐O‐Ce bonds under proton beam irradiation. The ORR activity observed for fabricated sample with above active surface layer was higher than that of conventional Pt/C (Pt/C = 0.2) and comparable to that of Pt‐CeOx nanowire/C (Pt/C = 0.2) fabricated by conventional methods. From the combination of microanalysis characterization and surface atomistic simulation, we concluded that the Pt‐O‐Ce bond was formed on defect‐rich regions of the CeOx nanowire and this leads to a maximized ORR activity on the fabricated sample. Based on all experimental data, it is concluded that the surface modification of CeOx nanowire support using proton beam irradiation is useful for a lowering the Pt content of the cathode with high ORR activity.